Pluricultural Competence and Translanguaging Practices: Insights from Thai BIPA Classes - Asteria, Prima Vidya; Yulianto, Bambang; Sodiq, Syamsul; Maneechukate, Siriporn; Sohnui, Suhailee (Forum for Linguistic Studies, 2025)
This study investigates the interplay of communication culture, pluricultural competence, and translanguaging in Indonesian and Thai BIPA (Bahasa Indonesia untuk Penutur Asing) classrooms. Data were collected through semi-structured interviews, focus group discussions, and classroom observations with 14 participants, including four experienced instructors and ten Thai learners of Indonesian. Thematic analysis revealed three interrelated themes: translanguaging as pedagogical practice, translanguaging and communication culture, and translanguaging and identity construction. Teachers used translanguaging to scaffold comprehension of complex grammatical structures and to highlight cultural norms such as "basa-basi" in Indonesia and "phuut taam marayaat" in Thailand, while learners reported increased confidence when allowed to mobilize Indonesian, Thai, and English flexibly. These findings demonstrate that pluricultural competence is enacted through communication culture and operationalized by translanguaging, which functions as a bridge connecting linguistic and cultural repertoires in multilingual, high-context societies. Theoretically, the study extends existing models of pluricultural competence by integrating communication culture as a critical dimension of language use and by providing evidence from Southeast Asia, where such research remains limited. Practically, the results highlight the need for teacher education and curriculum design to incorporate translanguaging and intercultural communication strategies, and for policymakers to move beyond monolingual assumptions toward inclusive, culturally responsive frameworks. By legitimizing translanguaging as both a pedagogical and cultural practice, this study demonstrates its potential to foster pluricultural competence, validate learners' linguistic identities, and strengthen intercultural understanding in BIPA education.